KONFLIK INDIA PAKISTAN; MENGULIK KONFLIK AGAMA DALAM KONSTALASI KENEGARAAN - Dirham Asese (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The long history that led to the conflict between India and Pakistan was based on religious differences, namely Hinduism and Islam. This article contains a discussion of religious conflicts that have occurred since British colonialism set foot in India. Colonization which resulted in violence against the natives of the Indian peninsula gave rise to a massive mass movement, but the resistance which had one mission, namely fighting colonialism, was divided due to differences in understanding of the influence of religious differences between Islam and Pakistan. The conflict between these two religions was very fierce and was exacerbated by the influence of British colonialism. This article uses a descriptive qualitative method with a historical approach. A historical approach is used to read conflict problems according to the history of the object's journey. Religious conflicts that lead to regional divisions are also influenced by complex political struggles, making this article borrow the theory put forward by social scientist Johan Galtum with the concept of conflict triangle theory. The results of the discussion in this article culminate in the attitude of religious adherents who want to avoid domination by other groups (Hindus and British colonialism) giving rise to behavioral responses that are resistant. Competition between groups separated according to religious identity as a result of British monopoly resulted in competition in the political field. The oppressive policy of colonialism required natives to take part in government so that competition occurred between high-ranking officials and each of the individuals they brought and succeeded in mobilizing a wave of masses of people who resisted and ended in violent conflict